Prohibition of riba: a study on the level of understanding of riba among Muslims educators in Sentul, Kuala Lumpur / Anis Rahimah Mohd Raizal - Mohd Raizal, Anis Rahimah (2021)
Believers! Do not swallow interest, doubled and redoubled, and be mindful of Allah so that you may attain true success (3:130). Based on the meaning from Surah Ali-Imran verse 130, where Allah SWT was commanding His servants to avoid from dealing with riba. As a faithful Muslim, we know that, in Islamic transaction, there are prohibited elements that we as Muslims cannot be involved and one of them is riba or known as usury. All the economic activities are legally permissible as long as these activities are based on Shariah law. Went we talked about riba, all Muslims will be said it is prohibited in Islam, however, in many occasions, not everyone understands well about riba. According to this research, I would like to do some research about the level of understanding of riba among Muslim educators. Then, in this study, I will be using the questionnaires survey to find the level of understanding of riba among Muslim educators in Sentul area. The results from the questionnaires will shows that either they really understand well about riba or just know the basic about riba. Thus, from doing this research, it also can help the Muslim educators can increase awareness on the prohibition of riba.